Effect of Double Injector on Combustion Process in a 396 Series Diesel Engine. Issue 3 (February 2020) - Liang, Yu; Zhou, Liying; Xu, Mingfei; Yao, Guwen
Abstract: The 396 series diesel engine has high performance, reliability and long service life, which has been widely used in many fields including ship, vehicle and industrial power unit. With the improved injection system and dual-injector in each cylinder, two injectors of the diesel can spray diesel at the same time; or one injector sprays ignition diesel and the other injector sprays biodiesel or alcohol fuel. A 3D combustion model of the 396 series diesel engine with flat-top convex basin combustion chamber is established by using the computational fluid dynamics software FIRE, and the combustion process when uniform 5-hole and 8-hole injectors and 4-hole dual-injector are adopted is simulated to compare and analyze the fuel spray, ignition start point, combustion pressure, combustion heat release rate, average temperature in cylinder and NO emission. Compared with the diesel engine adopting 8-hole injector, the diesel engine adopting 4-hole dual-injector has a wide spray space distribution area, high pressure and temperature in cylinder, and high thermal efficiency. The combustion process with injection duration of 26.84°CA, 22°CA and 20°CA for 396 series diesel engine adopting 4-hole dual-injector is simulated respectively, and the simulation result shows that the shorter injection duration can bring the higher maximum pressure and the maximum average temperature in cylinder, the shorter ignition delay period, the advanced ignition start point, the larger peak value of combustion heat release rate, the more concentrated combustion heat release, the higher NO emission. These three cases have almost the same accumulated heat release and the relatively complete fuel utilization. The proper injection duration shall be selected based on comprehensive consideration of the pressure in cylinder, effective power and NO emission. This research result is conductive to improve the combustion process of the 396 series diesel engine with the dual-injector and provides a basis for using biodiesel and alcohol fuel in the diesel engine.